Effect of Strike Activity on Firm Value - Davidson, Wallace N.; Worrell, Dan L.; Garrison, Sharon Hatten (Academy of Management Journal, 1988)
The article examines the stock market's reaction to labor management problems and employee strikes. A discussion is presented about various categories of strike costs and cumulative abnormal returns surrounding strike announcements and settlements. The author presents a definition of abnormal return and focuses on the effects of a strike or lockout on the overall value of a corporation. A regression model showing the relationship between strike activity and a firm's stock price is presented.